Enhanced 400-m sprint performance in moderately trained participants by a 4-day alkalizing diet: a counterbalanced, randomized controlled trial - Mirjam Limmer; Angi Diana Eibl; Petra Platen (Taylor & Francis Group, 2018)
Background Sodium bicarbonate (NaHCO3) is an alkalizing agent and its ingestion is used to improve anaerobic performance. However, the influence of alkalizing nutrients on anaerobic exercise performance remains unclear. Therefore, the present study investigated the influence of an alkalizing versus acidizing diet on 400-m sprint performance, blood lactate, blood gas parameters, and urinary pH in moderately trained adults. Methods In a randomized crossover design, eleven recreationally active participants (8 men, 3 women) aged 26.0 ± 1.7 years performed one trial under each individual's unmodified diet and subsequently two trials following either 4 days of an alkalizing (BASE) or acidizing (ACID) diet. Trials consisted of 400-m runs at intervals of 1 week on a tartan track in a randomized order. Results We found a significantly lower 400-m performance time for the BASE trial (65.8 ± 7.2 s) compared with the ACID trial (67.3 ± 7.1 s; p = 0.026). In addition, responses were significantly higher following the BASE diet for blood lactate (BASE: 16.3 ± 2.7; ACID: 14.4 ± 2.1 mmol/L; p = 0.32) and urinary pH (BASE: 7.0 ± 0.7; ACID: 5.5 ± 0.7; p = 0.001). Conclusions We conclude that a short-term alkalizing diet may improve 400-m performance time in moderately trained participants. Additionally, we found higher blood lactate concentrations under the alkalizing diet, suggesting an enhanced blood or muscle buffer capacity. Thus, an alkalizing diet may be an easy and natural way to enhance 400-m sprint performance for athletes without the necessity of taking artificial dietary supplements.